Larklight, or, The revenge of the white spiders!, or, To Saturn's rings and back! : a rousing tale of dauntless pluck in the farthest reaches of space - Reeve, Philip (Bloomsbury Children's Books: Distributed to the trade by Holzbrink Publishers, 2006)
In an alternate Victorian England, young Arthur and his sister Myrtle, residents of Larklight, a floating house in one of Her Majesty's outer space territories, uncover a spidery plot to destroy the solar system.